Pharmacological characterization of the involvement of protein kinase C in oscillatory and non-oscillatory calcium increases in astrocytes - Mitsuhiro Morita; Akira Nakane; Shohei Maekawa; Yoshihisa Kudo (Elsevier, 2015)
Evidence increasingly shows that astrocytes play a pivotal role in brain physiology and pathology via calcium dependent processes, thus the characterization of the calcium dynamics in astrocytes is of growing importance. We have previously reported that the epidermal growth factor and basic fibroblast growth factor up-regulate the oscillation of the calcium releases that are induced by stimuli, including glutamate in cultured astrocytes. This calcium oscillation is assumed to involve protein kinase C (PKC), which is activated together with the calcium releases as a consequence of inositol phospholipid hydrolysis. In the present study, this issue has been investigated pharmacologically by using astrocytes cultured with and without the growth factors. The pharmacological activation of PKC largely reduced the glutamate-induced oscillatory and non-oscillatory calcium increases. Meanwhile, PKC inhibitors increased the total amounts of both calcium increases without affecting the peak amplitudes and converted the calcium oscillations to non-oscillatory sustained calcium increases by abolishing the falling phases of the repetitive calcium increases. Furthermore, the pharmacological effects were consistent between both glutamate- and histamine-induced calcium oscillations. These results suggest that PKC up-regulates the removal of cytosolic calcium in astrocytes, and this up-regulation is essential for calcium oscillation in astrocytes cultured with growth factors.